EVALUATION OF TECHNOLOGICAL INTENSITY OF EXPORTS IN THE FORESTRY SECTOR - Silva,Orlando Monteiro da (2016)
ABSTRACT One of the fastest growing sectors in the domestic industry is the forestry, which has contributed significantly to economic development, job creation, income taxes, putting Brazil in a prominent position in the world market. This paper analyzes the evolution of the technological intensity of 12 main products exported by the sector, from 2000 to 2011. For that, utilizes an indicator called PRODY, which allows classifying different products according to their technological intensity or income content and considers the GDP per capita of exporting countries of each product, weighted by its revealed comparative advantage. It can be seen by the results, a continuous growth in all products' technology indicators and their decomposition into income effects, comparative advantage and joint effects, allowed to verify the main causes of this growth. Products with lower PRODY values are those that presented a higher evolution during the period studied. Products of higher processing, and those from pulp and paper industry, had greater technological advances, thanks to a joint effect, while the ones of lower processing, had a technological improvement due to the increase in GDP per capita in exporting countries. Sawn wood was the standout product, being the only one who proved to be dependent of comparative advantage effect, confirming that this industry has been reinventing itself and incorporating, in fact, more technology. This study revealed the importance of technological intensification to generate comparative advantage and be able to stand against international competition.